Strategi Aktif (Moving Average) Dan Strategi Pasif (Buy-And-Hold Strategi) Pada Pembentukan Portofolio Periode 2 Januari 2012 – 28 Desember 2012 - Loddy Li Putra; Werner R. Murhadi; Putu Anom Mahadwartha (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
This study aims to test whether active strategies with Moving averages are superior to the passive strategy Buy-and-Hold Strategy in stock portfolios formed based on LQ45 index. Research method used in the research begins with the collection of data which is then processed and analyzed. Subsequently Application ChartNexus used in order to form MA5&MA20 and MA10&30. Lastly the research  compare return from active strategies (moving average) and the passive strategy (buy-and-hold strategy). The results of this study indicate that passive strategy with buy-and-hold strategy is able to outperform the moving average active strategy when the market is bullish.